2007
DOI: 10.1148/radiol.2451061219
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Left Ventricular Remodeling and Analysis of Infarct Resorption in Patients with Reperfused Myocardial Infarcts by Using Contrast-enhanced MR Imaging

Abstract: Infarct size 24% or more of the LV area constitutes an important threshold to predict remodeling. Patients with remodeling develop disproportionate infarct resorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
87
2
7

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 25 publications
10
87
2
7
Order By: Relevance
“…We observed that infarct size and severity could be significant predictors of LV remodelling. Several clinical studies demonstrated that various parameters are predictive of remodelling, including anterior infarct location, patency of the infarctrelated artery, perfusion and functional parameters [4][5][6][7][8][9][10][11][12][13]. In agreement with these previous findings, the present study showed a number of baseline parameters predictive of remodelling, infarct severity demonstrating the best predictive value.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We observed that infarct size and severity could be significant predictors of LV remodelling. Several clinical studies demonstrated that various parameters are predictive of remodelling, including anterior infarct location, patency of the infarctrelated artery, perfusion and functional parameters [4][5][6][7][8][9][10][11][12][13]. In agreement with these previous findings, the present study showed a number of baseline parameters predictive of remodelling, infarct severity demonstrating the best predictive value.…”
Section: Discussionsupporting
confidence: 90%
“…Identification of lowrisk patients allows focusing the attention on higher-risk patients who would need a more aggressive therapy and clinical follow-up. Interestingly, the infarct size threshold that we found most effective was practically the same that has been reported using cardiac magnetic resonance imaging [8].…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations